Unveiling the cost differential: drivers behind the incremental costs of green office building construction in Kuala Lumpur - Foo, Shawn Shao Enn (2023)
Green building practices, aimed at minimizing environmental impact through resource efficiency, renewable energy use, green design and eco-friendly materials, have been globally introduced to address environmental concerns. However, the adoption of such practices varies across countries. In Malaysia, the adoption of green building practices remains low, with various studies highlighting barriers such as the lack of professionals, green technology, market awareness, government initiatives, and incentives, as well as human perceptions and behaviours. Yet, the consensus among researchers points to incremental costs as a significant hindrance. This research focuses on understanding the specific factors causing incremental costs in green office buildings in Malaysia. The choice of green office buildings as the research focus stems from their high resource consumption, including equipment and electricity for lighting, air handling units, and air conditioning. Face-to-face interviews were conducted with 20 respondents from diverse real estate professional backgrounds, including green certification organizations, architects, quantity surveyors, and a government green agency in Kuala Lumpur, Malaysia. Thematic analysis revealed four categories of incremental cost factors: active green design, passive green design, sustaining green equipment setup and maintenance, and indoor air quality management material. The study also identifies government incentives and education and awareness as crucial strategies for promoting green office adoption in Malaysia. The research contributes valuable insights for stakeholders, allowing real estate professionals and developers to make informed decisions and budget effectively. Policymakers can use these findings to enhance government incentives and support systems for green construction. Ultimately, this thesis aims to provide essential input for advancing the adoption of green office buildings in Malaysia.